Novel Quantum Encryption Algorithm Based on Multiqubit Quantum Shift Register and Hill Cipher - Khalaf, Rifaat Zaidan; Abdullah, Alharith Abdulkareem (Hindawi Ltd, 2014)
Based on a quantum shift register, a novel quantum block cryptographic algorithm that can be used to encrypt classical messages is proposed. The message is encoded and decoded by using a code generated by the quantum shift register. The security of this algorithm is analysed in detail. It is shown that, in the quantum block cryptographic algorithm, two keys can be used. One of them is the classical key that is used in the Hill cipher algorithm where Alice and Bob use the authenticated Diffie Hellman key exchange algorithm using the concept of digital signature for the authentication of the two communicating parties and so eliminate the man-in-the-middle attack. The other key is generated by the quantum shift register and used for the coding of the encryption message, where Alice and Bob share the key by using the BB84 protocol. The novel algorithm can prevent a quantum attack strategy as well as a classical attack strategy. The problem of key management is discussed and circuits for the encryption and the decryption are suggested.